TINGKAT STRES DAN KECEMASAN DALAM MENGHADAPI UJIAN MATEMATIKA - Minta Ito Simamora Simamora; Ulfa Ulfa Annisa Lubis; Eka Putri Yani; Dini Aulia (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This study aims to analyze the level of stress and anxiety among students in facing mathematics exams. The method used is descriptive quantitative with a survey technique involving 11 students. The research instrument was a Likert-scale questionnaire. The results show that most students experience anxiety and stress due to academic pressure, difficulty of material, and lack of preparation time. Social support also plays a role in reducing this pressure. This study suggests the need for stress management strategies and supportive instructional approaches in mathematics learning.